Optimization of the generation of oxidizing solution through dessalinizer waste electrolysis using experimental design (Research, Society and Development, 2021)
This work carried out studies about the use of the electrolysis process to produce oxidant solutions from water desalinators wastes for water disinfection. The experiment was conducted in laboratory scale. The oxidant solution were generated by electrolysis from wastes of water desalinators that presented concentrations of 3,8 x 104 mg  Cl-L-1. The electrolysis process lasted sixty minutes, at the end of which the pH, temperature and residual chlorine. The experiment investigated the characteristics of sodium hypochlorite production for disinfection purposes, four main factors were investigated: electrode types, distance between electrodes and sample concentration. Factorial design indicated that the generation of oxidizing solution will be favored when using the titanium anode and titanium or steel cathode, diluted tailings solution and electrode distance of 20 mm. It was observed that the maximum chlorine content of the generated oxidizing solution was 0.8 mgL-1, under the conditions evaluated. As a continuation of the experiments, the reaction kinetics to obtain a higher concentration of oxidizing solution will be evaluated, under the optimal conditions of the experiment, as well as the waste generated for feasibility study and application in the sanitation.